Video registration to geo-referenced imagery - Kasparis, Takis; Xu, Dongjiang (My University, 2004)
The problem of accurately registering an aerial video image to geo-referenced imagery has become more important in recent years. To achieve high efficiency, we propose a guided hierarchical searching scheme to augment the current geo-registration framework. The algorithm consists of three major steps. It the first step, the reference image and video frames are projected to a common coordinate system based on the telemetry. In the second step, feature points are extracted in the video and reference, and the coarse searching for the best match was performed on a feature points image pyramid, where the comparison process is only applied to the regions with feature points. In the final step, the precise transformation parameters are estimated using the Levenberg-Marquardt techniques, which results in a precise alignment of the video and reference. Compared with conventional blind comparison based on the normalized cross-correlation measure, the proposed approach differs because it applies a feature-based hierarchical searching scheme to quickly lead the matching process to the most likely portion in the reference and speed up the matching process. Experimental results that evaluate the developed approach using real world aerial video will be presented. The obtained results demonstrate that our proposed method can be used in a complete geo-registration system to provide accurate registration of the video frames.
Keywords: Algorithms; Correlators; Image analysis; Aerospace telemetry